Peningkatan Pengetahuan Tentang Perilaku Hidup Bersih Dan Sehat Serta Praktek Cuci Tangan Pakai Sabun Pada Saat Pandemi Covid-19 Di Kabupaten Pandeglang - Ucu Wandi Somantri; Heny Sasmita (Jurnal Pengabdian Pada Masyarakat, 2022)
INCREASED KNOWLEDGE ABOUT CLEAN AND HEALTHY LIVING BEHAVIORS AND THE PRACTICE OF WASHING HANDS WITH SOAP DURING THE COVID-19 PANDEMIC PANDEGLANG REGENCY. The rate of implementation of clean and healthy living behaviors in the community remains low due to the low level of socialization associated with the benefits and risks of not implementing clean and healthy living behaviors in daily life. Public health is disrupted due to the low level of socialization of clean and healthy lifestyles and the low willingness of the community to implement these lifestyles. This non-profit service is designed to enable communities to improve, protect and maintain health by making them aware, willing and able to actively participate in implementing clean and healthy living behaviors in their daily lives. This non-profit approach uses consultation to raise public awareness of clean, healthy lifestyles and handwashing techniques with soap. This event takes place in Kubang Kondang Village. The outcome of community service is knowledge growth after consultation, and there is a need to further improve communication, information and education (IEC) activities by involving more people to increase knowledge and attitudes about clean and healthy living and to improve handwashing.